'What makes a teacher': identity and classroom talk - Fajardo Castañeda, José Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The purpose of this study was to gain a closer understanding of how teachers’ identities are coconstructed and shaped through their interactions. The Conversation Analysis (CA) approach was used to collect and analyze naturally-occurring spoken interaction. An experienced foreign language teacher was video-recorded while she was teaching English to a mixed-intermediate adult class in a monolingual Spanish setting. A two-hour lesson was transcribed in detail following the transcription system adapted from van Lier (1988b) and Johnson (1995). Three extracts of classroom conversation were analyzed at a micro-level of interpretation in an emic-empirical perspective in terms of the IRF/E cycle (Initiation-Response-Feedback/Evaluation), turn-taking and repair. Results showed that the interactional flow of the lesson was constructed and maintained through asymmetric and empowered relations. The teacher seemed to determine, control and regulate most of the social actions that took place in the classroom, most of which were also entirely designed on a goal-oriented basis. The structure and implications of such an embedded institutional interaction might contribute to raising teacher awareness towards the effect of such a pedagogically restricted foreign language learning atmosphere.